Carpal tunnel syndrome caused by amyloid containing beta 2 microglobulin: a new amyloid and a complication of long term haemodialysis. - McClure, J (1986)
Three patients receiving long term haemodialysis treatment for chronic renal failure due to non-amyloid nephropathy developed the carpal tunnel syndrome requiring decompression surgery. The excised material contained amyloid, which by immunocytochemical techniques was shown to contain beta 2 microglobulin. This is, therefore, a new chemical form of amyloid whose deposition is likely to be the cause of osteoarticular and connective tissue disorders, which are being recognised with increasing frequency in patients receiving long term haemodialysis. Raised beta 2 microglobulin levels are known to occur in chronic renal failure, and the molecule is unable to cross conventional dialysis membranes. The importance of beta 2 microglobulin amyloidosis lies in the threat which it poses to the success of long term haemodialysis.